eCM 2018
DOI: 10.22203/ecm.v035a05
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass induced osteogenic differentiation of human adipose stem cells is dependent on cell attachment mechanism and mitogen-activated protein kinases

Abstract: Bioactive glasses (BaGs) are widely utilised in bone tissue engineering (TE) but the molecular response of cells to BaGs is poorly understood. To elucidate the mechanisms of cell attachment to BaGs and BaG-induced early osteogenic differentiation, we cultured human adipose stem cells (hASCs) on discs of two silica-based BaGs S53P4 (23.0 Na 2 O -20.0 CaO -4.0 P 2 O 5 -53.0 SiO 2 (wt-%)) and 1-06 (5.9 Na 2 O -12.0 K 2 O -5.3 MgO -22.6 CaO -4.0 P 2 O 5 -0.2 B 2 O 3 -50.0 SiO 2 ) in the absence of osteogenic suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…As previously reported, the decrease of cell number has been associated with borosilicate BaG ionic species induced restriction of cell proliferation and accompanying strong osteogenesis (Ojansivu et al, ). Moreover, boron ion induced effect on cell morphology has also been indicated by previous research (Brown et al, ; Rodriguez, Gonzalez, Rios, & Cambiazo, ), together with observed changes to cytoskeleton, cell adhesion, and signaling pathways (Ojansivu et al, , ). To the point, we observed a similar effect with borosilicate bioactive glass 2‐06 based BaG EM‐OM condition with strong osteocalcin production along with cubic cell morphology producing less oriented structures and truncated tubular growth.…”
Section: Discussionsupporting
confidence: 71%
“…As previously reported, the decrease of cell number has been associated with borosilicate BaG ionic species induced restriction of cell proliferation and accompanying strong osteogenesis (Ojansivu et al, ). Moreover, boron ion induced effect on cell morphology has also been indicated by previous research (Brown et al, ; Rodriguez, Gonzalez, Rios, & Cambiazo, ), together with observed changes to cytoskeleton, cell adhesion, and signaling pathways (Ojansivu et al, , ). To the point, we observed a similar effect with borosilicate bioactive glass 2‐06 based BaG EM‐OM condition with strong osteocalcin production along with cubic cell morphology producing less oriented structures and truncated tubular growth.…”
Section: Discussionsupporting
confidence: 71%
“…The differentiation of pluripotent murine embryonic stem cells to osteogenic cells was also stimulated, indicated by increased mineralized nodule formation, ALP activity, and osteoblast-associated gene expression (runx2/cbfa-1) when the cells were grown in a culture medium containing dissolution products from sol-gel 58S BG (60 mol% SiO2, 36 mol% CaO, 4 mol% P2O5) [58]. Osteogenic differentiation of human adipose stem cells (hASCs) cultured on two compositions of bioactive glass discs, S53P4 BG (23. SiO2, wt%), was induced, as the ALP activity and the expression of osteogenic marker genes runx2a and osterix were stimulated [59,60]. Dissolution products of a sol-gel glass with higher phosphate content (60 mol% SiO2, 28 mol% CaO, 12 mol% P2O5) also provoked mineralisation and increased mRNA expression of the osteogenic differentiation markers ALP, osteopontin and osteonectin from human dental pulp stem cells (hDPSCs) [61].…”
Section: Introductionmentioning
confidence: 99%
“…Such defects can be identified as the microcracks in TCP that propagate and coalesce under the effect of external stresses. In the single Schwab, & Spengler, 2009;Goldstein, 1987 and vinculin related intracellular mechanisms in hASCs leading to enhanced proliferation, Col-I production and osteogenesis (Ojansivu et al, 2018). Observations of the cross sections of the specimens after cell culture demonstrate the preferential colonization of the initial TCP zones in the composites.…”
Section: Discussionmentioning
confidence: 91%
“…Besides ionic compositions in growth medium, an important factor for osteogenic induction and ECM production of MSCs is the surface properties of the growth platform. Our recent results indicate that rougher bioactive glass surface, compared to smoother cell culture well, induces integrin and vinculin related intracellular mechanisms in hASCs leading to enhanced proliferation, Col‐I production and osteogenesis (Ojansivu et al, ). Observations of the cross sections of the specimens after cell culture demonstrate the preferential colonization of the initial TCP zones in the composites.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation